Serum miR-96-5p is a novel and non-invasive marker of acute myocardial infarction associated with coronary artery disease. Issue 2 (1st February 2022) - Ding, Hui; Chen, Wen; Chen, Xin
ABSTRACT: Acute myocardial infarction (AMI) is a severe cardiovascular disease. AMI associated with coronary artery disease (AMI-CAD) is a subtype of AMI, composed of AMI patients caused by CAD. This study aimed to evaluate the diagnostic value of miR-96-5p in AMI induced by coronary artery disease. Expression of miR-96-5p and BCL2L13 was evaluated by serum samples and cells utilizing Western blot and RT-qPCR assays. The diagnostic value of miR-96-5p in AMI-CAD was analyzed with a receiver operating characteristic (ROC) curves. The correlation between miR-96-5p and BCL2L13 was examined by Spearman's correlation analysis. The level of oxidative stress and apoptosis were estimated via relative commercial kit, flow cytometry apoptosis assay and TUNEL staining assay. Our study discovered that miR-96-5p was down-regulated while BCL2L13 was up-regulated in patients with AMI-CAD. miR-96-5p was a potential diagnostic parameter, which may help distinguish AMI-CAD patients from healthy controls. In vitro experiments, miR-96-5p expression was down regulated while BCL2L13 was up-regulated in hypoxic cardiomyocytes. After confirming the targeted link of miR-96-5p to BCL2L13 using luciferase reporter and RNA pull down assays, we discovered that miR-96-5p overexpression may restore oxidative stress and cell apoptosis induced by hypoxia treatment in H9c2 cells; meanwhile, co-transfection with BCL2L13 overexpressing plasmid might partly countervail the ameliorative effects of miR-96-5p on oxidative stress and apoptosis. Collectively, miR-96-5p may function as a potential diagnostic biomarker for AMI-CAD patients, and the up-regulation of miR-96-5p would ameliorate AMI-associated cardiomyocytes injury by targeting BCL2L13, hence contributing to the clinical treatment of AMI-CAD. Graphical abstract: uf0001